The Use of the Pressure Ulcer Scale for Healing (Push) in Patients with Pressure Ulcers and Multimorbidity: A Case Study - Aulia, Syifa Nurul; Harun, Hasniatisari; Rahayu, Urip (Journal of Nursing Care, 2025)
Pressure ulcers are a complication that becomes more complex when experienced by patients with multimorbidity such as Congestive Heart Failure (CHF), Chronic Kidney Disease (CKD), and thrombocytopenia. These conditions can lead to prolonged healing, high risk of infection, systemic complications, and even death. Interventions must be accompanied by appropriate tools to evaluate wound healing optimally. The Pressure Ulcer Scale for Healing (PUSH) is a tool for accurately, practically, and simply assessing the progression of pressure ulcers. However, its use for evaluating pressure ulcers remains limited. The objective to describe the use of PUSH in patients with pressure ulcers and multimorbidity. Method: This study used a case study design involving a 56-year-old patient with a grade III pressure ulcer on the buttocks measuring 121.5 cm2 with granulation tissue, minimal necrosis tissue, pus, and active bleeding. Wound progression was evaluated using PUSH over 4 days during wound care. The results that the PUSH score increased to 16 with a wound size of 150 cm2 moderate exudate, and extensive necrosis tissue. This indicates that the wound condition has not improved, prompting an evaluation of the wound care and factors hindering wound healing. Although PUSH aids clinical decision-making, it has limitations in assessing wound depth and systemic conditions as it only evaluates three parameters. The PUSH instrument is a simple and efficient tool for monitoring the healing of pressure ulcers and has the potential to indicate changes in wound condition as a result of an intervention, thereby aiding clinical decision-making. PUSH is recommended for routine use in clinical practice, while continuing to evaluate systemic conditions comprehensively and involving a multidisciplinary team.